Tissue specific expression profile of some immune related genes in Labeo rohita to Edwardsiella tarda infection. Issue 66 (July 2017) - Kole, Sajal; Anand, Deepika; Sharma, Rupam; Tripathi, Gayatri; Makesh, M.; Rajendran, K.V.; Kadam Bedekar, Megha
Abstract: Rohu ( Labeo rohita ), an Indian Major Carp (IMC) is an economically important aquaculture species in India. Inspite of the technological advances, infectious diseases caused by viruses, bacteria and parasites have been a major limiting factor in the development and profitability of fish farms. At present, information regarding the immune status of the Indian major carps is limited. This lack of knowledge is a major impediment for establishment of effective preventive measures against broad spectrum of infectious agents. The present study was undertaken to examine the modulation of few immune-regulatory genes: IgHC, NOD 1, TLR 22, iNOS and IL-1β during experimental infection of E. tarda in L. rohita to understand their role in pathogenesis. Rohu fingerlings were intra-peritoneally injected with Edwardsiella tarda (LD50 dose of 8.7 × 10 4 CFU/fish) and sampled for three immunologically important organs (kidney, liver and spleen) at different time intervals (zero hour or pre-challenge and 6 h, 12 h, 24 h, 48 h and 96 h post challenge). For absolute quantification of genes by real time RT-PCR, all the genes transcript were amplified from Poly I:C induced rohu lymphocytes and cloned in pTZ57R/T plasmid. Standard curves for each gene was generated from serially diluted plasmid bearing respective genes. Evaluation of copy number of different genes present in the tissue showed that the expression of IgHC, iNOS and IL-1β was highest in kidney followed by spleen and least in liver. While for NOD 1 and TLR 22 gene, liver showed higher expression than kidney and spleen. Further, the expression of IgHC, INOS, TLR 22, NOD 1 and IL-1β genes significantly differed (P < 0.05) in the E. tarda challenged fish when compared with pre-challenged control fish. Among the five genes we studied, the basal expression of TLR 22 gene was highest. The result also depicts that iNOS and NOD 1 are immediate responsive genes as their expression reached maximum level at 6–24 h post infection (hpi) after which the expression declined. In contrast, TLR 22 and IgHC gene transcript showed enhanced expression during the late phase of with maximum expression observed after 48 hpi and 96 hpi respectively. IL-1β, being the exception, showed high expression both at 24 hpi and 96 hpi. From this study, we conclude that these five immune genes have a definite role to play in the defense mechanism of host ( L. rohita ) against E. tarda. Highlights: Pathogenesis related to Edwardsiella tarda on Labeo rohita was studied. E. tarda exposure modulates TLR22, NOD1, IgHC, iNOS, IL-1β expression in L. rohita . Involvement of various immune pathways in disease processes was determined. Expression patterns demonstrated orchestration of various organs in host defences. Absolute quantization method used can be a referendum for various gene transcripts.